1978
DOI: 10.1042/bj1690543
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate carboxylase from a thermophilic Bacillus. Studies on the specificity of activation by acyl derivatives of coenzyme A and on the properties of catalysis in the absence of activator

Abstract: 1. Oxaloacetate synthesis catalysed by pyruvate carboxylase from a thermophilic Bacillus in the absence of acetyl-CoA required addition of high concentrations of pyruvate, MgATP(2-) and HCO(3) (-), and at 45 degrees C occurred at a maximum rate approx. 20% of that in the presence of a saturating concentration of acetyl-CoA. The apparent K(m) for HCO(3) (-) at pH7.8 was 400mm without acetyl-CoA, and 16mm with a saturating activator concentration. The relationship between reciprocal initial rate and reciprocal M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
2
26
1
Order By: Relevance
“…niduluns is only weakly activated by acyl derivatives of CoASH even in the presence of non-saturating concentrations of its substrates [4] and is subject to regulatory inhibition by Laspartate and 2-oxoglutarate [5]. These properties are generally similar to those described previously for pyruvate carboxylase from Succhuromyces cerevisiae [6,7] which has also been reported to have a cytosolic localisation [8]. Hence it has been suggested that the cytosolic and mitochondrial isoenzymes of pyruvate carboxylase may possess characteristically different regulatory properties [l 1.…”
supporting
confidence: 64%
“…niduluns is only weakly activated by acyl derivatives of CoASH even in the presence of non-saturating concentrations of its substrates [4] and is subject to regulatory inhibition by Laspartate and 2-oxoglutarate [5]. These properties are generally similar to those described previously for pyruvate carboxylase from Succhuromyces cerevisiae [6,7] which has also been reported to have a cytosolic localisation [8]. Hence it has been suggested that the cytosolic and mitochondrial isoenzymes of pyruvate carboxylase may possess characteristically different regulatory properties [l 1.…”
supporting
confidence: 64%
“…Previously, IC 50 values for the inhibition by l -aspartate for PC have been reported to be in the range of 0.6–4 mM, 10,11,21 while Dunn et al 22 reported that 10 mM l -aspartate only marginally inhibited the enzyme from Sinorhizobium meliloti . Thus, the K i value of 1.3 mM obtained for RePC in this study is at the lower end of the range.…”
Section: Discussionmentioning
confidence: 98%
“…There is, however, some evidence to suggest that this is not the case. First, Libor et al 21 showed that modification of the thermophilic Bacillus PC with trinitrobenzenesulfonate specifically inhibited acetyl-CoA-dependent enzyme activity but had no effect on the acetyl-CoA-independent activity or its inhibition by l -aspartate. Moreover, the presence of acetyl-CoA protected the enzyme against modification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the apparent K m for HCO 3 − observed with PC from B. Thermodenitrificans (32) was 16 mM in the presence of acetyl-CoA and the absence of acetyl-CoA resulted in a 25-fold increase in the K m for HCO 3 − (400 mM). Similar effects were observed in Re PC where the K m for HCO 3 − in Re PC determined in the presence of acetyl-CoA was 10.8 ± 0.4 mM, comparable to those for other bacterial PCs (33).…”
Section: Discussionmentioning
confidence: 99%